Identification and properties of a keratinase from Stenotrophomonas maltophilia N4 with potential application in biotechnology - Jankiewicz, Urszula; Frąk, Magdalena (Ecological Questions, 2018)
The bacterium Stenotrophomonas maltophilia N4 produces different extracellular proteases when cultured in a mineral medium with 1% of bird feathers. One of the enzymes was purified and characterized. The studied enzyme is a peptidase with keratinolytic activity. The optimal temperature for enzyme activity of the purified protein is 60°C, and its pH optimum 8.5. Its thermal stability is approximately 50% after two hours of preincubation at 55°C. Enzymatic activity is strongly inhibited by DFP and EDTA, indicating that the enzyme belongs to the metal-dependent serine proteases. Calcium, magnesium and manganese ions enhance the activity of the studied keratinase. The enzyme has broad substrate specificity; it hydrolyzes not only keratin, but also casein, gelatin and hemoglobin Considering the fact that the N4 bacteria are capable of using bird feathers as a source of organic nitrogen and carbon, and bearing in mind the stability and the broad substrate specificity of the studied enzyme, it appears that it may find application in various branches of biotechnology.